The peculiarities of formation of ukrainian-language communicative competence of foreign students - H. Matsiuk (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки, 2022)
The article deals with the peculiarities of learning the Ukrainian language by foreign applicants for higher education. Based on the personal practice, analysis, and generalization of scientific sources, the author outlines the peculiarities of the formation of Ukrainian-language competence of foreign students. The emphasis is placed on the formation of their communication skills as a necessary component of learning a foreign language.